Aging and Attentional Biases for Emotional Faces - Mather, Mara; Carstensen, Laura L. (Psychological Science, 2003)
We examined age differences in attention to and memory for faces expressing sadness, anger, and happiness. Participants saw a pair of faces, one emotional and one neutral, and then a dot probe that appeared in the location of one of the faces. In two experiments, older adults responded faster to the dot if it was presented on the same side as a neutral face than if it was presented on the same side as a negative face. Younger adults did not exhibit this attentional bias. Interactions of age and valence were also found for memory for the faces, with older adults remembering positive better than negative faces. These findings reveal that in their initial attention, older adults avoid negative information. This attentional bias is consistent with older adults' generally better emotional well-being and their tendency to remember negative less well than positive information.